Gut Microbiota Associated With Different Sea Lamprey (Petromyzon marinus) Life Stages - Mathai, Prince P.; Byappanahalli, Muruleedhara N.; Johnson, Nicholas S.; Sadowsky, Michael J. (Frontiers in Microbiology, 2021)
Sea lamprey (Petromyzon marinus), one of the oldest living vertebrates, have a complex metamorphic life cycle. Following hatching, sea lamprey (SL) transition to a microphagous, sediment burrowing larval stage, and after 2-10+ years the larvae undergo a dramatic metamorphosis, transforming into parasitic juveniles that feed on blood and bodily fluids of fishes; adult lamprey cease feeding, spawn and die. Since gut microbiota are critical for the overall health of all animals, we examined the microbiota associated with SLs in each physiological stage, each with unique feeding behaviors. We show that there were significant differences in the gut bacterial communities associated with the larval, parasitic juvenile, and adult life stages. The transition from larval to the parasitic juvenile stage was marked with a significant shift in bacterial community structure and reduction in alpha diversity. The most abundant SL-associated phyla were Proteobacteria, Fusobacteria, Bacteroidetes, Verrucomicrobia, Actinobacteria, and Firmicutes, with their relative abundances varying among the stages. Moreover, while larval SL were enriched with Fusobacteriaceae sp., Verrucomicrobiales sp. and Cetobacterium, members of the genera representing the fastidious, nutritional requirements, such as Streptococcus, Haemophilus, Cutibacterium, Veillonella and Massilia, were 3-4 orders of magnitude greater in juveniles than in larvae. In contrast, adult SLs were enriched with Aeromonas, Iodobacter, Shewanella, and Flavobacterium. Collectively, our findings show that bacterial communities in the SL gut are dramatically different among its life stages. How these communities change over time within and among life stages may shed more light on functional role of gut microbiota on lamprey growth and diet. Understanding the role that host-associated microbes (bacteria, fungi) play in SL fitness may provide new insights into the rearing of lamprey and the development of new lamprey control strategies.